PENGARUH FAKTOR TEKNIS ORGANISASI DAN FAKTOR KEPERILAKUAN ORGANISASI TERHADAP PENGEMBANGAN SISTEM PENGUKURAN KINERJA PEMERINTAH DAERAH ( Studi Empiris Pada Pemerintah Kabupaten Sleman ) - Rifai Arief Jadmiko (AKT 16 UMY 087, 2016)
The purpose of this study is to to prove the influence of organizational behavioral and technical factors for the development of performance measurement systems in order to improve the performance of local government.Population of this research is all Devices Working Unit (SKPD) in Sleman local government.The respondent is determined by using purposive sampling technique to obtain a representative sample . The sample used in this study is the structural officers (Echelon 3 , and 4 ) . The data in this study are primary data obtained from questionnaires distributed directly to the respondents. The hypothesis in this study were tested using multiple linear regression. The conclusions of this study indicate that the limitations of the information system did not prove a negative influence on the development of performance measurement systems. Management commitment a positive influence on the development of measurement systems. Employee training has positive influence on the development of performance measurement systems. Organizational culture has positive influence on the development of performance measurement systems . The Future studies are expected to conduct interviews to improve understanding of the answers given by the respondents , using quantitative and qualitative performance data , as well as expanding the research object , and the legislature to assess the attitude and commitment. Keywords: employee training, the limitations ofinformation systems, management commitment, organizational culture, the development ofperformance measurement systems.